Simple organizing - Michaels, Melissa, 1967- (Harvest House Publishers, 2018)
"Bring Order and Purpose to Every Room in Your Home. Getting organized can feel like an impossible task. But it doesn't have to be complicated. The things you actually use need a designated home. The rest of the stuff is clutter and needs to be removed. Once you've determined which is which, order can easily be maintained. Let bestselling author Melissa Michaels help you get organized with these 50 helpful ideas. Gain momentum by making progress, not perfection, your goal. Make the most of your space and create a home that works for your family. Reduce stress by decluttering and keeping only the things you regularly use. Featuring more than 300 easy organization tips that address every room, discover how simple and stress-free it can be to restore and maintain order in the space you call home"--